The chicken or the egg dilemma: intestinal dysbiosis in multiple sclerosis - Ochoa-Repáraz, Javier; Magori, Krisztian; Kasper, Lloyd H. (Annals of Translational Medicine; Vol 5, No 6 (March 28, 2017): Annals of Translational Medicine, 2017)
Recent findings suggest that the intestinal microbiota of patients suffering from relapsing remitting multiple sclerosis (MS) shows changes on the relative abundances of archaeal and bacterial genera. Although the richness and overall structure of the microbiota may be similar compared to the intestinal microbiota of healthy controls, elevated and reduced frequencies suggest a dysbiotic microbiota in MS. Over the past decade experimental evidence obtained in murine models of the disease highlighted the important relevance of the microbiota in the regulation of the immune system and in the severity of the disease. More recent findings on peripheral immune cells derived from human MS patients support the initial observations that changes in the microbiota may affect immunological pathways that could exacerbate disease. However, important questions remain to be answered. For instance, it is unclear whether dysbiosis precedes disease or, if in the contrary, an autoimmune disease such as MS can lead to gut dysbiosis. In this brief discussion, we speculate about this later possibility based on findings observed in murine models of disease. Further human studies are needed to answer the dilemma and determine specific immunomodulatory pathways that could have an impact on the therapeutic approaches to treat MS.